Identification and molecular mechanism of angiotensin-converting enzyme inhibitory peptides from Larimichthys crocea titin - Yue Fan; Zhipeng Yu; Wenzhu Zhao; Long Ding; Fuping Zheng; Jianrong Li; Jingbo Liu (Food Science and Human Wellness)
This study aimed to identify novel ACEI peptides from Larimichthys crocea titin using in silico approaches and to clarify the molecular interaction mechanism. The hydrolyzed peptides of titin were compared with known ACEI peptides in the AHTPDB and BIOPEP-UWM database. Furthermore, peptides were evaluated for their solubility, ADMET properties, △G (kcal/mol) values, and in vitro ACEI activity. Molecular mechanism of ACE-peptide was performed by molecular interactions and binding orientation study. The results revealed that IC50 values of Trp-Ala-Arg(WAR) and Trp-Gln-Arg(WQR) were (31.2 ± 0.8) and (231.33 ± 0.02) μmol/L, respectively. The docking interactions result suggested that ACE-WAR and ACE-WQR complexes have same binding site, including the residues LYS511, TYR520, TYR523, HIS353, and HIS513. Molecular docking of two tripeptides WAR and WQR with ACE studies predicted their binding site and clarified the interaction between ACE and its inhibitors. The molecular docking data are consistent with the ACE inhibitory activity of the studied peptides. The results showed that Larimichthys crocea titin may be a valuable source for developing nutraceutical food.